Body Shaming Through Social Media As a Digital Crime In The Era of Disruption - Mohamad Rusdiyanto U. Puluhulawa; Riski Husain (Universitas Negeri Gorontalo, 2021)
Digitalization has ushered in an era of disruption. The negative impact is body shaming. In the case of body shaming in Indonesia in 2018, “there were 966 cases of physical humiliation or body shaming handled by police from all over Indonesia throughout 2018. Most recently in 2019, public figures were also affected. No less surprising, this phenomenon does not only attack adults but also babies. The problem raised in this paper is what legal factors influence the rise of body shaming as a digital crime in the era of disruption. The approach method used is conceptual. In conclusion, the legal factors that influence the prevalence of body shaming are the substance of law and legal culture. In the aspect of legal substance, some areas have not been touched by current regulations, even though the legal realm is often used as a catalyst for digital body-shaming crimes. Meanwhile, in the aspect of legal culture, the problem of legal conflicts and low legal compliance are the main problems. To make matters worse, the attitude of the victim who prefers to ignore the treatment they receive without taking a fight justified by law makes the perpetrators of body shaming even wilder and more frontal, because law enforcers, as part of the legal structure, are unable to take action because this act falls under the complaint offense. Suggestions, improved regulations and the role of the press and the public to change the way they view body-shaming behavior